Debt management using the Sufficiency Economy Philosophy of military officials in 721st Artillery Regiment within the 72nd Artillery Brigade - Phraotha, Phattarakawin; Kerdphol Prasopsak, Wasita; Rattanasermpong, Mayuri (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
Debt management using the principles of the Sufficiency Economy Philosophy (SEP) involves applying SEP as a guideline for managing the debts of military personnel in the 721st Artillery Battalion of the 72nd Artillery Regiment. This study aims to examine the level of understanding of the Sufficiency Economy Philosophy among military officers and to assess their debt management practices based on SEP. The research population consisted of 159 military officers from the 721st Artillery Battalion, 72nd Artillery Regiment. The research tool used was a 25-item questionnaire. The data analysis included percentage values, means, and standard deviations. The results revealed that the military officers of the 721st Artillery Battalion had a high level of understanding of the key concepts of the Sufficiency Economy Philosophy. Additionally, their debt management practices based on SEP were also found to be at a high level. The mean scores, ranked from highest to lowest, were as follows: the dimension of moderation, the dimension of self-resilience, the dimension of rationality, the dimension of knowledge, and the dimension of ethics. The study identified five main strategies for debt management among military officers in the 721st Artillery Battalion: ceasing to incur further debt, summarizing all debt items, preparing detailed plans for debt repayment, obtaining funds with a lower interest rate than the debts being repaid, and refinancing by consolidating debts into a single repayment plan. The debt repayment plan should include prioritizing debts with higher interest rates and calculating the total repayment period, particularly when there are multiple debts involved.